Observations on the biology of a predatory nematode belonging to Diplogasteridae - Colagiero, M (2011)
Research partially funded by Bilateral Agreement CNR/CONCYTEC and MIPAF, Project BIOMED. Mr Nicola Salatino is gratefully acknowledged for the technical assistance provided during this study.